Do lifestyle factors influence risk of breast cancer recurrence in Korean women?: a cross-sectional survey - So-Jung Park; Hye-Ah Yeom (Korean Society of Women Health Nursing, 2022)
Purpose This study aimed to investigate the influencing factors of breast cancer recurrence by comparing the risk factors and lifestyle patterns related to breast cancer in Korean women with and without recurrence. Methods This cross-sectional survey comprised 241 Korean women diagnosed with breast cancer who had received follow-up treatment. Participants were recruited from a university hospital in Seoul and an online social media platform for breast cancer patients. Data were collected either via online or a paper survey, using a structured questionnaire that included general and disease-related characteristics and lifestyle behaviors. Data were analyzed using descriptive statistics, univariate analysis, and logistic regression. Results Recurrence of breast cancer was influenced by four factors; childbirth experience, consumption of green/yellow vegetables, drinking behavior, and recovery from fatigue after sleep.Prevalence of recurrent breast cancer was associated with no childbirth experience (OR=2.29, p=.010), fewer green/yellow vegetables (OR=0.71, p=.008), drinking behavior (OR=0.24, p=.001), and a lower level of recovery from fatigue after sleep (OR=0.51, p<.001). Conclusion Aside from having experienced childbirth, this study identified several modifiable factors that influence breast cancer recurrence. Increasing green/yellow vegetable intake, alleviating fatigue, and reducing alcohol intake are important. Intervention strategies in clinical research and practice can be applied to address risk factors and reduce the prevalence of recurrent breast cancer.